Protection challenges facing UNHCR in addressing the question of IDPs in the absence of explicit international legal framework: the case study of Pader District, Uganda - Buzoya, Kimenyi (My University, 2010)
For more than two decades now, the civil conflict that has pitted the Ugandan government against the rebel Lord’s Resistance Army (LRA) has caused significant internal displacement of people in the north of the country. Because political solutions have been slow to come to Africa’s ‘forgotten war’, humanitarian organizations have increasingly played a role in attempting to abate the effects of the war on Internally Displaced Persons (IDPs). One such organization is the United Nations High Commissioner for Refugees (UNHCR). Following a report by the then United Nations Under-Secretary-General for Humanitarian Affairs and Emergency Relief Coordinator, Jan Egeland in 2005 and invitation by the Government of Uganda, UNHCR officially started its work to assist IDPs in northern Uganda, including Pader district, in 2006. This study considers the protection challenges that UNHCR is faced with in trying to address the question of IDPs in the absence of explicit international legal framework. Specifically, the study attempts to understand how UNHCR is responding and assisting the government of Uganda to provide assistance and international protection to the IDPs in the context of the principle of sovereignty, which may be a source of tension between governments and transnational organizations, and a hindrance to effective implementation of UNHCR programmes. The study engages with the paradox of UN humanitarian intervention with IDPs and the challenges it faces as a result of its intervention. This research report relies on the data that was collected among UNHCR staff in Uganda in December 2008. Information was solicited from respondents through the open-ended in-depth interview technique, while additional data was gathered through the consultation of articles, reports and other written materials from UNHCR. The findings of the study suggest that UNHCR is faced with challenges to protection that are three-fold in nature; legal problems arising from gaps in the international legal framework for IDP protection and a lack of explicit international protection mandate, ineffective intervention challenges related to local dynamics that result in barriers to effective international protection of IDPs in Pader, as well as security dilemmas associated with the seemingly dire prospects for peace in northern Uganda in general, but particularly IDPs’ return to their previous villages that have spawned this situation. These problems hinder the effective implementation of UNHCR programmes at the local level. The report further suggest that the challenges of protection are less about the absence of a legal protection framework for internally displaced persons and more about contestation, conflict and competition between the state and transnational humanitarian organizations to earn the right to legitimacy in intervening on behalf of the internally displaced in the part of Uganda that is engulfed in war. In an environment where neither the state can claim autonomy nor transnational organisation can stick to political neutrality in delivering interventions, humanitarianism brings rewards for both a) government officials who may expect incentives from UNHCR to carry out work on behalf of the state, as well as b) UNHCR itself that wishes to appear to be the most effective in delivering intervention in the face of donor organizations and countries as well as the local population. In such conditions, both the ideals of sovereignty of the state and the political neutrality of the transnational organizations appear to fall away in either an overlap between the practices of sovereignty and humanitarianism, or the ineffective intervention that result in failure to balance the two in coordinating intervention efforts at the local level.